Trade of live bait in Portugal and risks of introduction of non-indigenous species associated to importation. - Sá, E. (2018)
Different invertebrate groups are often exploited on sediment shores and mudﬂats, including poly- chaetes, sipunculids, bivalves and crustaceans. The commercial importance of polychaetes and sipun- culids, that has increased in the early 2000's because of its use as a food source for the aquaculture sector and a growing demand of worms for use as sea angling bait, seems to be declining nowadays. In Portugal bait harvesting from natural populations became insufﬁcient to meet market demands and as a result, polychaetes and sipunculids have been imported in recent years. Due to this it was important to know the ways of the live bait import to Portugal, and to assess the risk of introduction of non-indigenous species associated to that live bait trade. The origin and quantities of imported live bait were deter- mined by examining the landing's records at Lisbon airport, from two periods: 2002e2003 and 2012 e2015. Live worms imported to Portugal arrived almost exclusively from China, USA and Vietnam. Monthly import data and bait registers at ﬁsh auction landings were signiﬁcantly correlated, showing that bait captures and imports are directly related to higher bait demand. In addition, the risk of live bait's importation as an introduction vector for non-indigenous species was evaluated by examining the bait boxes content. Five worm species were identiﬁed in bait boxes with foreign species: Glycera dibranchiata, Namalycastis rhodochorde, Perinereis cultrifera, Perinereis linea, and Sipunculus (Sipunculus) nudus. The examination of bait boxes in Portugal suggested that there is a low risk of associated hitchhiker species introduction and dissemination, mostly because of packaging procedures, which should be advised. The same is not true to the non-indigenous live bait species.